A toolkit to support ventilated children and young people in children's hospices. Issue 2 (1st September 2011) - Cooke, Alison; Harris, Sam
Abstract : Children and young people who require Long Term Ventilation have heralded a new challenge for children's hospices across the UK. There has been growing recognition of the increasing numbers of those who are ventilator dependant and ongoing discussion about the appropriateness of their referral to children's hospice services. In addition there has been concern about the lack of consistency in caring for these children and young people and the need for further advice and guidance. A significant and growing number of young people with long term palliative conditions are now receiving Long Term Ventilation as part of their palliative care trajectory. Many of these young people are now surviving into adult life and are likely to transition into adult hospice care as their disease progresses. It is therefore likely that the issues, teaching pack, templates and information contained within the toolkit will also be highly relevant to adult hospice services. The Children's Hospices UK (CHUK) Ventilation Toolkit has been funded through money from the first round DH £30 Million for Children's Palliative Care. It has been created by a team of professionals from across the UK, led by Alison Cooke, Director of Care at Rainbows Hospice for Children and Young People in Leicestershire and David Widdas, Consultant Nurse for Children and Young People with Complex Health Needs in Coventry and Warwickshire.